2019
DOI: 10.1111/psyp.13447
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inspiratory threshold load on cardiovascular responses to controlled breathing at 0.1 Hz

Abstract: Slow, deep breathing is being used as a self‐management intervention for various health conditions including pain and hypertension. Stimulation of the arterial baroreceptors and increased vagal modulation are among the proposed mechanisms for the therapeutic effects of slow, deep breathing. We investigated whether adding inspiratory threshold load can enhance the cardiovascular responses to controlled breathing at the frequency of 0.1 Hz, a common form of slow, deep breathing. Healthy volunteers (N = 29) perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
56
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(62 citation statements)
references
References 69 publications
4
56
2
Order By: Relevance
“…We recently showed that using an ITL during SDB further increases blood pressure variability at the frequency of breathing followed by increased respiratory sinus arrhythmia (RSA). Although we found no further change in baroreflex sensitivity by using ITL, with the baroreflex operating within a larger range of blood pressure fluctuations, the application of ITL during SDB can enhance stimulation of the arterial (high‐pressure) baroreceptors (Gholamrezaei et al., 2019). These responses may explain the beneficial effects of loaded SDB in patients with hypertension and may also extend to pain as stimulation of the baroreceptors and autonomic modulation during SDB are proposed to have hypoalgesic effects (Jafari et al., 2017).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…We recently showed that using an ITL during SDB further increases blood pressure variability at the frequency of breathing followed by increased respiratory sinus arrhythmia (RSA). Although we found no further change in baroreflex sensitivity by using ITL, with the baroreflex operating within a larger range of blood pressure fluctuations, the application of ITL during SDB can enhance stimulation of the arterial (high‐pressure) baroreceptors (Gholamrezaei et al., 2019). These responses may explain the beneficial effects of loaded SDB in patients with hypertension and may also extend to pain as stimulation of the baroreceptors and autonomic modulation during SDB are proposed to have hypoalgesic effects (Jafari et al., 2017).…”
Section: Introductionmentioning
confidence: 76%
“…The flow‐independent threshold load (Threshold PEP, Respironics Inc., NJ, US) was used and set to a load of 10 cmH 2 O based on our previous study (Gholamrezaei et al., 2019). A nose clip was used to help the participant to breathe only through the mouth during loaded SDB.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Deeper breathing during SDB causes greater fluctuations in intrathoracic pressure, cardiac filling, and blood pressure along the respiratory cycle, which results in greater RSA. 25,26,42,48,56 The magnitude of RSA and vagal activity is further increased when breathing at one's particular "resonance frequency," which on average lies around.1 Hz, and at which resonance properties of the baroreflex system may further enhance RSA and cardiac vagal activity. 61,62 Finally, cardiac vagal activity was found to be higher when breathing with lower compared to higher inspiration/expiration ratios (eg, 3s/7s vs 7s/3s, 60 or 2s/8s vs 8s/2s 9 ), that is, when expiration is long relative to inspiration.…”
mentioning
confidence: 99%